PTU-036 Screening of type II diabetic patients for liver fibrosis with fibroscan in primary care. (June 2019) - Siu, Wilson; Stephen, Megan; Shand, Stuart; Dundas, Pauline; Mukhopadhya, Ashis
Abstract : Introduction: In 2016, European Association for the Study of the Liver (EASL) recommended the presence of non-alcoholic fatty liver disease (NAFLD) should be looked for in Type II diabetic patients as they are at high risk to develop liver fibrosis. Our prospective cohort study aims to examine the practicality of screening Type II diabetic patients for liver fibrosis and to compare different liver fibrosis scores. Methods: For a 10 weeks period, a hepatology specialist nurse from Aberdeen Royal Infirmary attended the Type II Diabetic Clinic at 3 general practices. Unselected patients at the clinics were given information leaflets before consenting for Fibroscan and blood testing. Different liver fibrosis scores including NAFLD fibrosis, Fibrosis-4 (FIB-4) and AST to Platelet Ratio Index (APRI) scores were calculated on the day of Fibroscan. Clinically significant fibrosis (≥F2) was defined as liver stiffness measurement (LSM) > 7 kPa and advanced liver fibrosis/cirrhosis (F3 and F4) was defined as LSM > 12 kPa. Patients with LSM >7 kPa were given lifestyle modification advices including diet, exercise and alcohol intake. Full 'liver screen' was performed for these patients and they were seen in the hepatology clinic with follow-up Fibroscan. Results: 49 patients (mean age: 67.6 ±12.2, mean BMI: 30.5 ±6.4 and male: 55%) were recruited in the study after excluding 4 patients due to excess alcohol intake (n=1), known liver cirrhosis (n=1) and body habitus (n=2). 22/49 (45%) patients had LSM >7 kPa. 12/14 (86%) patients who had follow-up fibroscan had decreased LSM. 37/40 (93%) patients had a score >-1.455 which indicated indeterminate/advanced fibrosis scores based on previous studies. In our study, all liver fibrosis scores performed poorly at diagnosing clinically significant fibrosis (>7 kPa): NAFLD score (AUROC=0.57), APRI score (AUROC=0.52) and FIB-4 score (AUROC=0.42). NAFLD score (AUROC=0.81) had the best diagnostic accuracy for advanced fibrosis (>12 kPa) compared to APRI score (AUROC=0.76) and FIB-4 score (AUROC=0.73). The best NAFLD Cut-off score for advanced fibrosis was ≥0.502 with a sensitivity of 100% and specificity of 54%. Conclusions: In this small cohort study, there was a high prevalence of indeterminate/advanced NAFLD fibrosis scores in unselected type II diabetic patients. This strategy could lead to significant number of hepatology referrals to hospitals if used as a screening test. The NAFLD score was the best performing panel for advanced fibrosis in this cohort. Lifestyle modification advice given by the hepatology specialist nurse led to significant improvement in patients' repeat liver stiffness measurements.